Tradisi Keagamaan Sebagai Bentuk Pelestarian Budaya Masyarakat Jawa Pada Masa Pandemi - Dwi Susanto; Ainur Rosidah; Deivy Nur Setyowati; Guntur Sekti Wijaya (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2021)
Petiken is one of the villages in Gresik Regency that still preserves religious traditions. In its implementation, this tradition is an annual routine. Religious traditions are still carried out by the community even during the COVID-19 pandemic. This study aims to (1) find out the religious traditions in Petiken, Driyorejo, Gresik Villages before the COVID-19 and (2) know the religious traditions in Petiken Village, Driyorejo, Gresik as a form of cultural preservation of the community during the COVID-19 pandemic. This research uses qualitative methods with data collection through interviews and observations. The results of this study were (1) religious traditions in Petiken Village, Driyorejo, Gresik before the COVID-19 were carried out normally, both annual traditions and weekly routines and (2) religious traditions in Petiken Village,the early days of the arrival of COVID-19 which made all traditions temporarily abolished, the PSBB period with the implementation of some traditions underwent a change, and a new normal period by re-implementing all traditions by complying with health protocols.